Elucidation of the canker and scab symptoms on pumpkin caused fusarium species. - Nagao, Hideyuki
Scabs or cankers on the surface of pumpkins are not recognized as "diseased" by ordinary consumers because these scabs or cankers are generally not softened and are seemed to be recovered after injuring. By the inoculation test, mechanical injury was the sole causal agent to induce scab and canker of pumpkin. Isolates from scabs were identified as Fusarium spp.